2001
DOI: 10.1128/aac.45.3.883-892.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Resistance of Staphylococcus aureus , Selected Enterobacteriaceae , and Pseudomonas aeruginosa after Single and Multiple In Vitro Exposures to Ciprofloxacin, Levofloxacin, and Trovafloxacin

Abstract: The phenotypic resistance of selected organisms to ciprofloxacin, levofloxacin, and trovafloxacin was defined as a MIC of >4 g/ml. The dynamics of resistance were studied after single and sequential drug exposures: clinical isolates of methicillin-susceptible and methicillin-resistant Staphylococcus aureus (MSSA and MRSA), Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae, Serratia marcescens, and Pseudomonas aeruginosa were utilized. After a single 48-h exposure of a large inoculum to four times t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 22 publications
6
36
1
Order By: Relevance
“…Those authors reported a successful outcome at 24 months for 12 of 12 patients in the rifampin group, compared with 7 of 12 in the placebo group (P ϭ 0.02). This study is problematic for a number of reasons: (i) it contained only 15 patients with PJI, 8 of whom received rifampin-based therapy; (ii) it was not analyzed by intention to treat, as when one includes the 9 patients who were excluded from the analysis due to having received Ͻ85% of the study drug, the cure rates are not significantly different between the two groups (P ϭ 0.10); and (iii) the control arm received a treatment known to have a significant chance of failure, because a course of 3 to 6 months of ciprofloxacin monotherapy for S. aureus often leads to resistance (556). Observational studies of this approach are very heterogeneous; however, they report success rates ranging from 57% (551) to Ն85% (549,550).…”
Section: Prosthetic Joint Infectionmentioning
confidence: 99%
“…Those authors reported a successful outcome at 24 months for 12 of 12 patients in the rifampin group, compared with 7 of 12 in the placebo group (P ϭ 0.02). This study is problematic for a number of reasons: (i) it contained only 15 patients with PJI, 8 of whom received rifampin-based therapy; (ii) it was not analyzed by intention to treat, as when one includes the 9 patients who were excluded from the analysis due to having received Ͻ85% of the study drug, the cure rates are not significantly different between the two groups (P ϭ 0.10); and (iii) the control arm received a treatment known to have a significant chance of failure, because a course of 3 to 6 months of ciprofloxacin monotherapy for S. aureus often leads to resistance (556). Observational studies of this approach are very heterogeneous; however, they report success rates ranging from 57% (551) to Ն85% (549,550).…”
Section: Prosthetic Joint Infectionmentioning
confidence: 99%
“…It predicted that resistant subpopulations would not emerge when a lowdensity culture with a low probability of mutants was exposed to a simulated clinical dosing regimen (400 mg every 12 h) or when a high-density culture with a higher probability of mutants was exposed to the high concentrations of an experimental regimen designed to rapidly eradicate grlA mutants, followed by the lower concentrations of the clinical regimen. The validity of these predictions was confirmed with in vitro system experiments.In this study we extend our observations to levofloxacin, which has been shown to select resistant S. aureus variants less frequently than ciprofloxacin (10,14,24,34). This was done by modeling the effect of simulated clinical and experimental levofloxacin regimens on two S. aureus strains and their grlA mutants in the in vitro system.…”
mentioning
confidence: 99%
“…In this study we extend our observations to levofloxacin, which has been shown to select resistant S. aureus variants less frequently than ciprofloxacin (10,14,24,34). This was done by modeling the effect of simulated clinical and experimental levofloxacin regimens on two S. aureus strains and their grlA mutants in the in vitro system.…”
mentioning
confidence: 99%
“…Although it was possible to select fluoroquinolone-resistant isolates by performing serial passages in the presence of subinhibitory concentrations of various fluoroquinolones (Gilbert et al,2001), it was considered relatively difficult (Smith, 1986). In contrast to these laboratory observations, it was believed that resistance to fluoroquinolones emerged often in clinical isolates.…”
Section: Adverse Reactionsmentioning
confidence: 93%